The Role of Women's Leadership Characteristics in Shaping Job Autonomy and Its Effects on Employee Innovation Performance - Dewi, Puspa; Alviani, Devi (Universitas Muhammadiyah Yogyakarta, 2023)
Research aims: This study investigates the impact of women's leadership traits on employee innovation performance and the role of job autonomy as an intermediary.Design/Methodology/Approach: This study used a quantitative approach with a cross-sectional design, focusing on micro-level analysis, with 323 employees from a Pekanbaru Public Health Center (Puskesmas) as the target population. One hundred seventy-five samples were obtained using Cluster Random Sampling, and the SEM statistical test and Smart PLS 4.0 software were utilized for quantitative analysis.Research findings: Women's characteristic leadership supports the creation and development of employee innovation performance. It will be better if the provision of work autonomy accompanies it.Theoretical Contribution/Originality: Developing a job autonomy theory covers procedural autonomy, soft skills, and decision-making. Scheduling autonomy includes time flexibility and technical tasks. Autonomy within job criteria is assessed through task priority, management, and performance.Practitioners/Policy Implications: The research highlights the importance of work autonomy in Pekanbaru Health Centers, highlighting the role of women's leadership characteristics and proving that women possess the same abilities as men, thereby supporting employee innovation performance.Research Limitations/Implications: The study suggests that future research could benefit from a longitudinal design to assess theory constructs over time, considering the limitations of cross-sectional designs and the limited sample size of Pekanbaru City Health Center employees, allowing for a more comprehensive analysis.